What is the effect of foreign direct investment inflows on economic growth in Pakistan? An empirical analysis in the light of religious sectarianism as catalyst for terrorism - Ayesha Serfraz (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2017)
FDI inflows play an important role in bringing growth and development to emerging economies. Pakistan is also heavily dependent on FDI inflows for achieving a high growth rate but the main obstacle being faced by Pakistan is increasing number of terrorist activities. Although there is a vast literature available which throws light on FDI lead economic growth relation based on terrorism but this study will surely add new dimensions to the ever increasing research on overseas investment in developing countries, specifically Muslim countries, by correlating religious sectarianism with FDI and economic growth. The present study analyses the effect of religious sectarianism on the relationship between FDI inflows and economic growth in Pakistan for the period of 1989-2016. For measuring sectarian terrorism, data of sectarian violence in Pakistan is taken for carrying out the empirical analysis. This study explores an empirical relationship by testing a two-way causality between FDI inflows and economic growth of Pakistan, using the techniques of Johansen Cointegration and VECM model. For testing two way causality, two separate models are constructed; in the first model FDI inflows is taken as a dependent variable with economic growth and sectarian terrorism as independent variables. In second model, economic growth is taken as a dependent variable and FDI inflows along-with sectarian terrorism are taken as independent variables. ADF and KPSS tests have been applied to check the stationarity status of variables included in dataset. Later Johansen Cointegration test has been applied twice for checking the strength of Cointegration. The results of VECM and system equation model show that the first model is more practical as the F-statistic is strong in case of first model as compared to second model 2 but the purpose is achieved and a two-way causality has been confirmed by empirical analysis. Wald test and Granger Causality tests have been applied to check the exogeniety and causality respectively. The results show that FDI is not weakly exogenous whereas the second model concludes that GDP is weakly exogenous. The same results are confirmed by Granger Causality test.
Keywords: 330; FDI inflows; Economic Growth; Sectarianism; Johansen Cointegration; Pakistan